Antioxidant Response in Duckweed After Exposure to Secondary Effluent from Municipal Wastewater Treatment Plant, Elazig, Turkey - Tatar, Sule Yuksel; Obek, Erdal; Yildirim, Nuran Cikcikoglu (Springer, 2017)
The aim of this study is to evaluate the effects of the effluent of Elazig Municipality Wastewater Treatment Plant on the oxidative defense capacity of aquatic plants (Lemna minor L. and Lemna gibba L.). For this purpose, malondialdehyde (MDA), glutathione (GSH), oxidized glutathione (GSSG), vitamin A (retinol), vitamin E (alpha-tocopherol), and vitamin C (Ascorbic acid) levels were determined by the HPLC (high performance liquid chromatography) in the control groups and the groups adapting to reactors fed with discharge water. The depletion of vitamins (A, E, and C), decrease of GSH/GSSG ratio, and increase of MDA that reflect a precarious state of the cell in L. minor L. and L. gibba L. were observed after exposure to wastewater. It can be suggested that the selected biomarkers are useful in understanding the biochemical mechanisms of the secondary effluents from wastewater treatment plant in L. minor L. and L. gibba L. as early warning indicators.
Keywords: Non-enzymatic antioxidants; MDA; Wastewater treatment; L. gibba L.; L. minor L.